Kota Berkelanjutan: Analisis Efektivitas Penerapan Smart Mobility dan Smart Living untuk Menciptakan Happy City di Kota Jakarta - Anis Wulandari; Uras Siahaan; Margareta Maria Sudarwani (Fakultas Teknik - Universitas Bung Karno, 2023)
Contemporary technological developments have given birth to a smart city concept that is able to respond to urban problems through the use of information and communication technology. On the other hand, aspects of happiness indicators have become part of city performance, so studies have emerged that link happiness with the quality of life of city residents. In line with the sustainable city development paradigm, in recent years, the Jakarta Special Capital Region government has developed public transportation such as commuterline, Transjakarta, MRT and LRT which is supported by technology in payment systems and departure schedules to improve services for its users. However, it is not enough to provide satisfaction for users due to problems with ticket sensors, payment via vending machines and inappropriate arrival time management. The aim of this research is to analyze the effectiveness by comparing the plans that have been determined with the results in implementing two smart city pillars, namely smart living and smart mobility to create a Happy City in the city of Jakarta. This research uses a descriptive quantitative approach with observation and the use of questionnaires. From the results of the discussion, it was found that the majority of users stated that it had not been achieved or that development was still needed in terms of waiting time range, ease of technology, security and comfort. Meanwhile, city residents as users stated that they were quite happy, showing satisfaction with comfort and security.